Comprehensive Utilization Pattern of the Bohai Rim Coastline Using the Restrictive Composite Index Method - Yun Zhang; Tong Wu; Yuanzhi Ye (Complexity)
Coastlines play an important role in human activity and economic development. Reasonably allocating shoreline resources and addressing contradictions between ecological protection and development are critical issues. In this study, positive and negative factors affecting the natural, environmental, and socioeconomic status of the coastal zone while considering land and sea effects were comprehensively analyzed using ecological theories and methods, and an improved restrictive composite index model was constructed. We quantitatively analyzed the comprehensive utilization pattern of the Bohai Rim coastline, China, in terms of the coastline utilization type and spatial agglomeration characteristics. The comprehensive utilization pattern of the Bohai Rim coastline is as follows: ecological areas are present in the north and south, and industrial areas are present in the east and west. Industrial production areas along the coastline are mainly distributed in the East Liaodong and Bohai bays, and ecological protection areas are located in the estuaries of the Liaohe and Yellow River. The improved restricted comprehensive index method model weakens the interaction among variables and makes the calculation results closer to the real situation. The results of the comprehensive utilization pattern of Bohai Rim coastline obtained by quantitative evaluation are of great significance for the coordinated development of coastline ecological protection and development and utilization.